A soil bacterium Rhizobium borbori and its potential for citrinin-degrading application - Kanpiengjai A. (2017)
© 2015, Springer-Verlag Berlin Heidelberg and the University of Milan. Red mold rice is the fermentation product of ordinary white rice with various Monascus spp. and is popular in Asian countries as a food additive and for its beneficial effects on human health. However, most Monascus spp. not only produce valuable secondary metabolites, such as monacolin K, but also the mycotoxin citrinin, which limits the applicability of red mold rice in medical therapy and food production. The aim of this study was to isolate, screen and identify citrinin-degrading bacteria that can be used for citrinin degradation in industrial and medical applications. A total of 96 bacteria were obtained from 74 samples of soil, water and wastewater collected from Chiang Mai, northern Thailand. Of these, 14 isolates exhibited growth in a mineral medium containing 5 ppm crude citrinin, among which only five demonstrated citrinin-degrading ability without any loss of monacolin K after culture at 30 °C for 72 h. Isolates PS21 and PS45 degraded citrinin the fastest of all five isolates and also retained the lowest residual citrinin concentration. Based on 16S rRNA gene sequence analysis, isolates PS21 and PS45 were identified as Enterococcus cloacae and Rhizobium borbori, respectively. When R. borbori PS45 and E. cloacae PS21 were cultured in a mineral medium containing 5 ppm pure citrinin at 30 °C for 120 h, the residual citrinin contents were 1.83 and 2.82 ppm, respectively. The citrinin-degrading activities of both isolates were found predominantly in the cell-free supernatant. Based on its higher citrinin-degrading activity and safety, we propose R. borbori PS45 as a suitable microorganism for citrinin reduction in red mold rice products.